2011
DOI: 10.1007/s10897-011-9424-3
|View full text |Cite
|
Sign up to set email alerts
|

Giving and Withholding of Information following Genomic Screening: Challenges Identified in a Study of Primary Care Physicians in Estonia

Abstract: The use of predictive genomic information to improve medical care remains a contentious topic. However, it is generally agreed that the potential of genomics to improve medicine relies on medical care providers' ability to effectively communicate and put in context the meaning of test results. As the amount of information available increasingly outstrips providers' ability to offer qualified judgments on what the information means, consumers inevitably will be faced with test results of uncertain significance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Of the 62 final articles included, 36 studies were quantitative studies,27–62 13 were qualitative studies,3 63–74 9 were randomised controlled trials75–83 and 4 were mixed-methods study70 84–86 (online supplemental table 5). The selected studies were conducted in USA (n=20), UK (n=19), Canada (n=11), Australia (n=6), Asia (n=4), New Zealand (n=1) and South Africa (n=1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 62 final articles included, 36 studies were quantitative studies,27–62 13 were qualitative studies,3 63–74 9 were randomised controlled trials75–83 and 4 were mixed-methods study70 84–86 (online supplemental table 5). The selected studies were conducted in USA (n=20), UK (n=19), Canada (n=11), Australia (n=6), Asia (n=4), New Zealand (n=1) and South Africa (n=1).…”
Section: Resultsmentioning
confidence: 99%
“…40 Sixty-four GPs surveyed in a separate study also expressed concerns on giving patients a false sense of security or inducing unnecessary anxiety over genetic results. 62 Moreover, resistance to adopt genetic testing was also exacerbated by organisational barriers such as rigid administration infrastructure, 66 lack of clinical guidelines on genetic practice 43 52 53 and limited access to labs that perform PGx testing. 84 Additional resources could also incur more cost that could overburden the healthcare system.…”
Section: Genetic Education and Interventionsmentioning
confidence: 99%
“…Continued education and training of health professionals is also highly important so they are qualified to effectively apply genomic tests and communicate the garnered results to their patients. While family physicians are optimistic about envisioning genomics in their everyday practice they too recognize that additional training is necessary [ 123 ]. To prepare the physicians, genomic healthcare workshops are prepared, covering topics on genetic risk scores, pharmacogenomics, and genetic counselling.…”
Section: Future Outlook For Personalized Medicine In Estonia and Beyondmentioning
confidence: 99%
“…Whilst the personalized and predictive aspects of this approach rely on biomarkers for early diagnosing or for identification of at-risk patients, the preventive and participatory aspects rely on intervention at the primary care level where educating both patients and healthcare providers is crucial. The findings of a study of the expectations of Estonian primary care physicians regarding the use of genomic information in primary care practice suggested that there is an eagerness to apply genomic information in practice, as well as a willingness to improve their knowledge base in genetics and genomics [ 73 ]. However, there is a need for policies and guidelines, as well as clinical decision support, for determining where, when and how to use test results.…”
Section: Use Of Genetic Data In Health Carementioning
confidence: 99%